Trans-papillary bilio-pancreatic stenting: When how and which stent - Cappello, Annalisa; Landi, Rosario; Gerges, Christian; Cennamo, Vincenzo; Costamagna, Guido; Tringali, Andrea (Frontiers in Gastroenterology, 2023)
Nowadays, stenting malignant biliary stenosis (extrahepatic or hilar), benign biliary stenosis, and pancreatic duct stenosis in chronic pancreatitis as well as stenting for prophylaxis of post- endoscopic retrograde cholangiopancreatography pancreatitis and for failed extraction of biliary stones or endoscopic papillectomy are the many common challenges for a bilio-pancreatic endoscopist. The purpose of this review is to provide a practical approach to bilio-pancreatic stenting indications and techniques. Having a thorough understanding of stenting indications and techniques, for a bilio-pancreatic endoscopist means being able to develop a tailored approach for each clinical scenario depending on the type of stent used. Biliary stents, in fact, vary in diameter, length, and composition, making it possible to give each patient personalized treatment.